1999
DOI: 10.1002/(sici)1097-461x(1999)74:2<223::aid-qua17>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Bent-bond versus separated-bond models: A spin-coupled survey for a few organic and inorganic systems

Abstract: Fully‐variational spin‐coupled calculations on various systems (ScCH 2+, TiCH 2+, C2H2, N2, and C2H4) are used to illustrate factors which favor either the bent bond model or the symmetry separated (σ+π) model of multiple bonding. For systems that are not well described by a single mode of spin coupling, the degree of flexibility in the total spin function can be more important than the number of degrees of freedom in the orbitals. Furthermore, restricting the number of correlated electrons has a more deleteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A discussion of the pros and cons of such alternative interpretations of [1.1.1]propellane might not seem so dissimilar to comparisons between the alternative σ-π and bent-bond descriptions of multiple carbon–carbon bonds. 45 47 However, the magnetic shielding interpretation of bonding in this molecule would not change as it does not require the use of a specific wavefunction—as we have demonstrated, the analyses of B3LYP and CASSCF(2,2) isotropic shielding contour plots lead to essentially the same conclusions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A discussion of the pros and cons of such alternative interpretations of [1.1.1]propellane might not seem so dissimilar to comparisons between the alternative σ-π and bent-bond descriptions of multiple carbon–carbon bonds. 45 47 However, the magnetic shielding interpretation of bonding in this molecule would not change as it does not require the use of a specific wavefunction—as we have demonstrated, the analyses of B3LYP and CASSCF(2,2) isotropic shielding contour plots lead to essentially the same conclusions.…”
Section: Discussionmentioning
confidence: 64%
“…Of course, the electronic structure of [1.1.1]­propellane could be interpreted in more than one way, for example, using localized MOs or different VB approaches, placing more or less emphasis on orbital shapes, overlaps, and ionic structures. A discussion of the pros and cons of such alternative interpretations of [1.1.1]­propellane might not seem so dissimilar to comparisons between the alternative σ-π and bent-bond descriptions of multiple carbon–carbon bonds. However, the magnetic shielding interpretation of bonding in this molecule would not change as it does not require the use of a specific wavefunctionas we have demonstrated, the analyses of B3LYP and CASSCF­(2,2) isotropic shielding contour plots lead to essentially the same conclusions.…”
Section: Discussionmentioning
confidence: 73%
“…There has been considerable discussion in the literature on the nature of the multiple bonds in C 2 H 4 and C 2 H 2 , beginning with the early suggestion of Slater that these bonds were bent bonds . This topic has been discussed in detail by Karadakov et al and Ogliaro et al who reported SCGVB calculations on these two molecules. Penotti and Cooper provided additional insights into the nature of the multiple bonds in C 2 H 2 (as well as N 2 ).…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…Alongside the use of the full spin space, which proves so useful, for example, in distinguishing clearly between aromatic, antiaromatic and nonaromatic π-electron systems, a key feature of SCGVB theory is the variational flexibility of the orbitals, given that they are expanded in the full molecular basis set without any constraints. It has been shown (see ref and references therein) that the relative energetic importance of the different numbers of spin and orbital degrees of freedom leads, in some instances but not in others, to a preference for bent bond descriptions over the corresponding σ–π separated solutions. Bent bonds have also been observed in a somewhat different context, namely for the in-plane σ bonding in strained ring systems.…”
Section: Insights Into the Electronic Structure Of Moleculesmentioning
confidence: 99%